Measuring Organizational Safety Climate Using NOSACQ-50 - Hashim, A. H. (2015)
Nordic Safety Climate Questionnaire is a diagnostic and intervention tool to evaluate the status and progress of safety climate in an organization and can be used as a bench marking tool at the group, company, sector, national and international level, generating possibilities for cross-level knowledge sharing.